"But the art of youth is to resist!": the collective reorganization of rural youth social movements and the creation of Youth Struggle Platform (Polis (Santiago), 2023)
In a scenario of political crisis and dismantling of public policies, driven by the presidential veto of the PL Assis de Carvalho, of support for family farming, and the dismantling of the MDA, Incra and other agencies, rural youth social movements have proposed the so-called Youth PL, or Youth Struggles Platform, which aims to aggregate the new agendas as well as the historical demands of rural youth. The present article aims to analyze the process of re-articulation and the agency of rural youth social movements, hampered since the coup of 2016, through the construction of the Youth PL, started in 2021. The methodology follows the qualitative approach, where, through interviews and documentary analysis, we will analyze how the movements have reorganized themselves in the political field (political parties, mandates, IPs etc.) and unified agendas around the elaboration of a PL.
Keywords: social movements; rural youth; political participation; Youth Struggle Platform